High Fasting Glycemia Predicts Impairment of Cardiac Autonomic Control in Adults With Type 2 Diabetes: A Case-Control Study - Silva, Lucas Raphael Bento; Gentil, Paulo; Seguro, Camila Simões; de Oliveira, Gabriela Teles; Silva, Maria Sebastiana; Zamunér, Antônio Roberto; Beltrame, Thomas; Rebelo, Ana Cristina Silva (Frontiers in Endocrinology, 2021)
Introduction: Type 2 diabetes (T2D) is characterized by a metabolic disorder that elevates blood glucose concentration. Chronic hyperglycemia has been associated with several complications in patients with T2D, one of which is cardiac autonomic dysfunction that can be assessed from heart rate variability (HRV) and heart rate recovery (HRR) response, both associated with many aspects of health and fitness, including severe cardiovascular outcomes. Objective: To evaluate the effects of T2D on cardiac autonomic modulation by means of HRV and HRR measurements. Materials and Methods: This study has an observational with case-control characteristic and involved ninety-three middle-aged adults stratified into two groups (control group - CG, n = 34; diabetes group - DG, n = 59). After signing the free and informed consent form, the patients were submitted to the evaluation protocols, performed biochemical tests to confirm the diagnosis of T2D, collection of R-R intervals for HRV analysis and cardiopulmonary effort test to quantify HRR. Results: At rest, the DG showed a reduction in global HRV (SDNN= 19.31±11.72 vs CG 43.09±12.74, p < 0.0001), lower parasympathetic modulation (RMSSD= 20.49±14.68 vs 52.41±19.50, PNN50= 4.76±10.53 vs 31.24±19.24, 2VD%= 19.97±10.30 vs 28.81±9.77, p < 0.0001 for both indices) and higher HRrest when compared to CG. After interruption of physical exercise, a slowed heart rate response was observed in the DG when compared to the CG. Finally, a simple linear regression showed that fasting glycemia was able to predict cardiac autonomic involvement in volunteers with T2D. Conclusion: Patients with T2D presented lower parasympathetic modulation at rest and slowed HRR after physical exercise, which may be associated with higher cardiovascular risks. The findings show the glycemic profile as an important predictor of impaired cardiac autonomic modulation.